Epidemiology, Clinical Features, and Prescribing Patterns of Irritable Bowel Syndrome in Taiwan - Lai, Yu-Tung; Chen, Chung-Yu; Bair, Ming-Jong (Frontiers in Pharmacology, 2021)
Background Understanding the prescribing patterns could better inform IBS management and health policy. However, there is no study on prescribing patterns of IBS in Taiwan. To evaluate the epidemiology, clinical features, and prescribing patterns of IBS in Taiwan. Methods This population-based cross-sectional study was performed by retrieving claim data from National Health Insurance Research Database (NHIRD) between 2011 and 2018 in Taiwan. Patients who were diagnosed with IBS during 2012-2018 and more than 20 years old were included. The annual incidence and prevalence of IBS were estimated. The characteristics and prescribing pattern were evaluated among IBS population. Results A total of 1691596 patients diagnosed with IBS were identified from 2012 to 2018. The average annual incidence and prevalence of IBS in Taiwan were calculated as 106.54 and 181.75 per 10,000 population. The incidence and prevalence showed a decreasing trend from 2012 to 2018. Hypertension, dyslipidemia, chronic liver disease, peptic ulcer, gastroesophageal reflux disease (GERD), anxiety, and sleep disorder were the prevalent comorbidities in IBS population. Antispasmodics was the most frequently prescribed medication class. The proportion of consultation for IBS and the prescribing rates of all medications were decreased considerably after IBS diagnosis. Conclusions The incidence and prevalence of IBS showed a decreasing trend from 2012 to 2018. Antispasmodics was widely used for IBS management by the Taiwanese population. The prescribing rates of all medications for IBS were decreased considerably after IBS diagnosis. These findings provided the whole picture of the epidemiology and prescribing pattern of the IBS population in Taiwan.